2008
DOI: 10.1108/09596110810873534
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hotel industry budgetary practice

Abstract: Purpose -The purpose of this paper is to provide an insight into budgetary practice in UK-based hotel organizations and an update on previous survey work in this area. The research aims to cover a broad range of budgeting issues, including: the process used in setting budgets, monitoring and review of the budgetary processes, and the human aspects of the budgeting process. Design/methodology/approach -This research used a census-based questionnaire of hotel organizations' finance directors. The questionnaire c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
19

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(57 citation statements)
references
References 10 publications
3
34
1
19
Order By: Relevance
“…A literatura nacional e a internacional apontam distintas características para o processo orça-mentário (Schmidgall e Ninemeier, 1986Umapathy, 1987;Schmidgall, Borchgrevink e Zahl-Begnum, 1996;Schmidgall e DeFranco, 1998;Jones, 1998Jones, , 2008aJones, , 2008bSubramaniam, Mcmanus e Mia, 2002;Winata e Mia, 2005;Prendergast, West e Shi, 2006;Yuen, 2006;Rankin, Schwartz e Young, 2008;Pavlatos e Paggios, 2009;Oak e Schmidgall, 2009;Derfuss, 2009;Steed e Gu, 2009;King, Clarkson e Wallace, 2010;Uyar e Bilgin, 2011;Castro et al, 2012). Essas principais características do processo orçamentário apontadas na literatura estão ilustradas no quadro 1.…”
Section: Revisão De Literatura: Orçamentounclassified
“…A literatura nacional e a internacional apontam distintas características para o processo orça-mentário (Schmidgall e Ninemeier, 1986Umapathy, 1987;Schmidgall, Borchgrevink e Zahl-Begnum, 1996;Schmidgall e DeFranco, 1998;Jones, 1998Jones, , 2008aJones, , 2008bSubramaniam, Mcmanus e Mia, 2002;Winata e Mia, 2005;Prendergast, West e Shi, 2006;Yuen, 2006;Rankin, Schwartz e Young, 2008;Pavlatos e Paggios, 2009;Oak e Schmidgall, 2009;Derfuss, 2009;Steed e Gu, 2009;King, Clarkson e Wallace, 2010;Uyar e Bilgin, 2011;Castro et al, 2012). Essas principais características do processo orçamentário apontadas na literatura estão ilustradas no quadro 1.…”
Section: Revisão De Literatura: Orçamentounclassified
“…In the UK, Jones (2008b) concluded that none of the approaches (bottom-up, top-down and combination/participatory) was predominant. Uyar & Bilgin (2011) and Steed & Gu (2009) observed that in Turkey and the United States, respectively, most hotels use the combination/participatory approach.…”
Section: Discussionmentioning
confidence: 99%
“…The survey applied was developed from the fundamental characteristics identified in the literature review Ninemeier, 1987 and1989;Schmidgall et al, 1996;Schmidgall & DeFranco, 1998;Jones, 1998Jones, , 2008aJones, and 2008bSubramaniam et al, 2002;Winata & Mia, 2005;Yuen, 2006 and2007;Pavlatos & Paggios, 2009;Steed & Gu, 2009;Uyar & Bilgin, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations